School Principal Supervision in Improving Guidance and Counseling Teachers Management at SMAN 4 and SMAN 11 Banda Aceh - Aidil, Arnita; Murniati, Murniati; Niswanto, Niswanto (FKIP Universitas Lampung, 2021)
This research aims to identify a clear vision of the principal supervision in improving the counseling teachers management. Using the descriptive method with a qualitative approach, this research data collecting techniques were interview, observation, and documentation study. The subjects were the supervisor, principal, vice principal of curriculum affair, and counseling teachers. The results show that the Programs were designed and carried out at least twice a year at the beginning of even and odd semester. The supervision implementation is carried out by the principal or supervision team and the counseling teachers. The principal supervision refers to counseling teacher ability in making counseling programs including the annual program, semester program, implementation plan of classical guidance services (RPL-BK), and empowering students with counseling services. The supervision techniques are conducted by visiting the counseling room individually and in groups, meeting, discussion, and sharing experiences. Keywords: the supervision of the principal, management, counseling teachers DOI: 10.23960/jpp.v11.i2.202125